ECONOMIC VIABILITY OF DEMOLITION RECYCLED WASTES USED DURING THE CONSTRUCTION OF THE SUBFLOOR OF A BUILDING LOCATED IN THE EAST SIDE OF THE CITY OF SÃO PAULO - Paschoalin Filho, João Alexandre; Storopoli, João Henrique; Duarte, Eric Brum Lima (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The civil construction industry is responsible for a considerable environmental impact, whether the demand for natural raw materials or the generation of waste from its activities. The Resolution 307 of 5 July 2002 of the National Environmental Council classified construction and demolition wastes into different classes according to their physical characteristics, and forms to submit its disposal. This resolution highlights that construction waste can´t be disposed of on domestic wastes in landfills, slopes, water bodies, and areas protected by law. Thus, it is the responsibility of the waste generator provide the correctly destination of the produced waste according to their classification. This research presents the economic feasibility of using recycled demolition waste in replacing natural material for the base implementation of the third basement subfloor a building in Sao Paulo. Through the conducted studies it was concluded that the use of recycled waste has led to a cost 64 % less than using natural material as possible to reduce the costs of acquisition and transportation of natural material.